2020
DOI: 10.1038/s41598-020-62960-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Analysis of Heterogeneous Tuberculosis Pulmonary Pathology in Non-Clinical Animal Models using Deep Convolutional Neural Networks

Abstract: Efforts to develop effective and safe drugs for treatment of tuberculosis require preclinical evaluation in animal models. Alongside efficacy testing of novel therapies, effects on pulmonary pathology and disease progression are monitored by using histopathology images from these infected animals. to compare the severity of disease across treatment cohorts, pathologists have historically assigned a semi-quantitative histopathology score that may be subjective in terms of their training, experience, and persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…(A) Blinded histopathology analysis by a board-certified pathologist using a semiquantitative method based on histology scores ( 56 ). (B) Quantitative analysis plus the SEM using pathologist-assistive software called LIRA (lesion image recognition and analysis [ 21 ]) developed for pulmonary pathology of M. tuberculosis -infected C3HeB/FeJ mice, employing convolutional neural networks trained using a machine learning approach, and (C) visual representation of the results generated by LIRA for digital images of pulmonary lesions of drug-treated C3HeB/FeJ mice. The various lesion classifications are displayed in a color overlay depicting type I core (red), type I rim (blue), type II (green), type III (yellow), healthy tissue (pink), miscellaneous (purple), and empty slide (no color).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(A) Blinded histopathology analysis by a board-certified pathologist using a semiquantitative method based on histology scores ( 56 ). (B) Quantitative analysis plus the SEM using pathologist-assistive software called LIRA (lesion image recognition and analysis [ 21 ]) developed for pulmonary pathology of M. tuberculosis -infected C3HeB/FeJ mice, employing convolutional neural networks trained using a machine learning approach, and (C) visual representation of the results generated by LIRA for digital images of pulmonary lesions of drug-treated C3HeB/FeJ mice. The various lesion classifications are displayed in a color overlay depicting type I core (red), type I rim (blue), type II (green), type III (yellow), healthy tissue (pink), miscellaneous (purple), and empty slide (no color).…”
Section: Resultsmentioning
confidence: 99%
“…Second, digital scans of hematoxylin and eosin (H&E)-stained tissue sections were evaluated using a new pathologist-assistive software called LIRA (lesion image recognition and analysis [ 21 ]), designed and developed for digital image analysis of pulmonary pathology in M. tuberculosis -infected C3HeB/FeJ mice. The LIRA results showed that all three DprE1 inhibitors were able to halt the progression of the lung pathology from treatment start by preventing the development of destructive type II neutrophilic lesions (which account for 25% of the total lung area in the untreated controls after 8 weeks) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Percent lesion calculations were integrated into the same algorithm and calculated from tissue area and lesion area as designated by the ROI and lesions detected. Lesion identification and quantification were then reviewed and edited by a pathologist as needed 79 .…”
Section: Methodsmentioning
confidence: 99%